Caracterização de osteoblastos diferenciados de células-tronco mesenquimais da medula óssea de ratos espontâneamente hipertensos (SHR) - Cursino, Natalia Manrique [UNESP] (2014)
Hypertension is a systemic risk factor for several diseases including reduction of bone mass by increasing bone resorption and reducing bone formation. Considering that bone formation results from osteoblast activity, the aim of this study was to assess the phenotypic and genotypic characteristics of osteoblastic cells differentiated from MSCs of SHR. Bone marrow was harvested from SHR femurs and MSCs were selected by adherence to plastic cell culture and differentiated into osteoblasts by culturing in osteogenic medium until subconfluence. Then, the cells were subcultured at a density of 2x104 cells / well in 24 well plates. Cells from Wistar rats were used as control. Cells responses were evaluated by assaying proliferation, alkaline phosphatase activity (ALP), mineralized matrix formation and the gene expression of the osteoblastic markers: runt-related 1) runt-related transcription fator 2 (RUNX2), 2) Osterix (OSX) 3) Alkaline phosphatase (ALP), 4) Bone morphogenetic protein 2 (BMP2); 5) Bone sialoprotein (BSP), 6) Osteocalcin (OC), 7) Osteopontin (OPN), 8) and Collagen type 1 alpha (COL), in addition to the gene expression of β1 and β2 adrenergic receptors. Data were compared by ANOVA followed by Tukey test and the level of significance was 5% (p ≤ 0.05). SHR derived osteoblasts showed changes in osteoblastic phenotype, exhibiting in all periods reduced cell proliferation, ALP activity and mineralized matrix formation. The gene expression of all bone markers was also lower in SHR compared with Wistar in many periods. The gene expression of the β2 adrenergic receptor was greater in SHR in all periods and it was not detected the expression of β1receptor either in SHR or Wistar. Based on these results, we conclude that osteoblasts differentiated from SHR MSCs exhibit reduced or delayed in the differentiation process. We also suggest...